Functional analysis of the fractalkine gene promoter in human aortic smooth muscle cells exposed to proinflammatory conditions. (29th July 2014) - Gan, Ana‐Maria; Butoi, Elena; Manea, Adrian; Pirvulescu, Monica Madalina; Stan, Daniela; Simion, Viorel; Calin, Manuela; Simionescu, Maya; Manduteanu, Ileana
<x xml:space="preserve">Abstract</x> Fractalkine (Fk) and its receptor CX3C receptor 1 contribute effectively to the atherosclerotic process, mediating the recruitment of leukocytes and promoting the interactions between monocytes/macrophages and smooth muscle cells (SMCs). As Fk expression is significantly increased in SMCs during atherogenesis, we aimed to uncover the detailed molecular mechanisms of transcriptional regulation of the Fk gene. For this purpose, we cloned and characterized the human Fk promoter, and studied the specific roles of different transcription factors in its regulation in human aortic SMCs activated by interferon‐γ. In silico analysis of the Fk promoter indicated the presence of binding sites for various inflammatory modulators, such as nuclear factor‐κB (NF‐κB), signal transducer and activator of transcription (STAT)1/STAT3, and activator protein‐1. Using a luciferase reporter plasmid, we identified a 2046‐bp region spanning the transcriptional start point of the Fk gene, which has strong constitutive promoter activity in SMCs. The effects of interferon‐γ on both Fk reporter activity and endogenous transcription were abolished by silencing NF‐κB, STAT1, and STAT3. Transient overexpression of p65/NF‐κB and STAT1/STAT3 increased Fk promoter activity, whereas c‐Jun/activator protein‐1 overexpression had no effect. The results obtained with chromatin immunoprecipitation assays revealed the existence of physical interactions of p65 and STAT1/STAT3 with the predicted elements of the Fk promoter. Moreover, Fk‐promoted monocyte chemotaxis was dependent on the janus kinase–STAT pathway. Investigation of the detailed molecular mechanisms by cloning and characterizing potential transcriptional response elements has identified the Fk regulatory mechanism in activated human SMCs.